Gut Dysbiosis and Adaptive Immune Response in Diet-induced Obesity vs. Systemic Inflammation - Pindjakova, Jana; Sartini, Claudio; Lo Re, Oriana; Rappa, Francesca; Coupe, Berengere; Lelouvier, Benjamin; Pazienza, Valerio; Vinciguerra, Manlio (Frontiers in Microbiology, 2017)
A mutual interplay exists between adaptive immune system and gut microbiota. Altered gut microbial ecosystems are associated with the metabolic syndrome, occurring in most obese individuals. However, it is unknown why 10-25% of obese individuals are metabolically healthy, while normal weight individuals can develop inflammation and atherosclerosis. We modelled these specific metabolic conditions in mice fed with a chow diet, an obesogenic but not inflammatory diet - mimicking healthy obesity, or Paigen diet - mimicking inflammation in the lean subjects. We analysed a range of markers and cytokines in the aorta, heart, abdominal fat, liver and spleen, and metagenomics analyses were performed on stool samples. T lymphocytes infiltration was found in the aorta and in the liver upon both diets, however a significant increase in CD4+ and CD8+ cells was found only in the heart of Paigen-fed animals, paralleled by increased expression of IL-1, IL-4, IL-6, IL-17 and IFN-gamma. Bacteroidia, Deltaproteobacteria and Verrucomicrobia dominated in mice fed Paigen diet, while Gammaproteobacteria, Delataproteobacteria and Erysipelotrichia were more abundant in obese mice. Mice reproducing human metabolic exceptions displayed gut microbiota phylogenetically distinct from normal diet-fed mice, and correlated with specific adaptive immune responses. Diet composition thus has a pervasive role in co-regulating adaptive immunity and the diversity of microbiota.